THE EFFECT OF MASS MEDIA ABUSES AS REFLECTED IN DELLILO’S WHITE NOISE - Hairunnisa, Widya; Soraya, Andi Inayah; Irmawati, Irmawati (JURNAL ILMU BUDAYA, 2020)
This research intends to elaborate the effect of mass media abuses through Dellilo’s White Noise. Therefore, the researchers analyzed how the effect of mass media abuses influence the character through the novel. In analyzing this research, the researchers used genetic structuralism approach as the grand theory and concept of mass media as the supporting theory. Moreover, the writer used qualitative method and descriptive analysis method in analyzing the data. The result of this research is the writers finds there are three effect of mass media abuses such as (1) consumerism, (2) drug abuses, and (3) violence.